Pengaruh CSR Disclosure dan Kinerja Lingkungan pada Kinerja Keuangan dengan Kepemilikan Asing sebagai Pemoderasi - Sari, Wayan Mila Cahya; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 34 No 8 (2024)DO - 10.24843/EJA.2024.v34.i08.p04, 2024)
Issues related to environmental aspects really need to considered to improve financial performance. The purpose of this study was to determine how the influence of CSR disclosure and environmental performance on financial performance moderated by foreign ownership.  This research was conducted on companies that are members of the SRI-KEHATI Index of the BEI for the period 2017-2020.  The number of samples using purposive sampling technique as many as 12 companies with 48 observations.  Data collection was carried out using the non-participant observation method.  The analytical techniques used are descriptive statistics, classical assumptions, and moderated regression analysis (MRA).  The test results show that CSR disclosure has a positive effect on financial performance.  Environmental performance has a positive effect on financial performance.  Foreign ownership can moderate the effect of CSR disclosure and environmental performance on financial performance.  Financial performance; CSR disclosure;, environmental performance; foreign ownership